2019
DOI: 10.1038/s41433-019-0461-8
|View full text |Cite
|
Sign up to set email alerts
|

Serous retinal detachment in preeclampsia and malignant hypertension

Abstract: Objectives To compare and evaluate the characteristics of hypertensive choroidopathy with serous retinal detachment in preeclampsia and malignant hypertension (HTN) and explore choroidal ischemia as a pathogenesis using multimodal imaging. Methods A retrospective multicenter case series. Medical charts were reviewed. Clinical characteristics and multimodal imaging, including optical coherence tomography (OCT) and OCT angiography (OCTA), were evaluated. Results Fifty-three eyes of 29 preeclampsia patients and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
1
38
0
3
Order By: Relevance
“…20 Hypertensive chorioretinopathy is seen more commonly in younger patients with acute elevations in blood pressure and is associated with a poor prognosis if left untreated. It has been reported in conditions such as malignant hypertension, 13,20 pre-eclampsia, 21 eclampsia, 22 acute or chronic renal failure, 23,24 renal artery stenosis, 25 and adrenal carcinoma. 26 These conditions are all medical emergencies that require immediate treatment.…”
Section: Significance Of Hypertensive Chorioretinopathymentioning
confidence: 99%
“…20 Hypertensive chorioretinopathy is seen more commonly in younger patients with acute elevations in blood pressure and is associated with a poor prognosis if left untreated. It has been reported in conditions such as malignant hypertension, 13,20 pre-eclampsia, 21 eclampsia, 22 acute or chronic renal failure, 23,24 renal artery stenosis, 25 and adrenal carcinoma. 26 These conditions are all medical emergencies that require immediate treatment.…”
Section: Significance Of Hypertensive Chorioretinopathymentioning
confidence: 99%
“…We read with delight the paper "Serous retinal detachment in preeclampsia and malignant hypertension" [1], with striking demonstration of choroidal and choriocapillaris (CC) ischemia leading to Serous Retinal Detachments (SRDs). We also wish to call attention to the fact that these findings are potentially of utmost importance for agerelated macular degeneration (AMD), and in particular the reticular macular disease (RMD) phenotype with subretinal drusenoid deposits (SDD).…”
Section: To the Editormentioning
confidence: 99%
“…4 We hypothesize that the choroidal expansion seen in hypertensive emergency could also have contributed to the hemorrhage. 2 This patient was also at higher risk for SRD given the presence of nephrotic syndrome caused by focal segmental glomerulosclerosis, which decreases vascular oncotic pressure. This can cause an imbalance in the Starling equation, favouring movement of fluid from the choroidal capillaries to the subretinal space.…”
mentioning
confidence: 89%
“…OCT angiography imaging suggested that choroidal circulation hypoperfusion from hypertension was a key mechanism in hypertensive choroidopathy and ischemia, predisposing patients to subsequent SRD. 2 Gaudric et al previously reported on ischemia and venous stasis as a mechanism for SRD by allowing fluid exudation through the retinal pigment epithelium and subretinal accumulation. 3 In our patient, the choroidal ischemia shown on FA and indocyanine green angiography suggests the role of impaired choroidal vascular perfusion and interstitial fluid extension into the subretinal space as an underlying mechanism.…”
mentioning
confidence: 99%